Effectiveness of Wizer.me and MindMup assisted Remap-TPS in improving communication skills - Hafidhatul Furqoniyah Jauhari; Muhammad Ilham A’raafi; Siti Zubaidah; Abdul Gofur (University of Muhammadiyah Malang, 2025)
Communication skills are important to support students in conveying information orally or in writing. This research aims to analyze the effectiveness of the Remap-TPS learning model assisted Wizer.me website and MindMup to improve students’ communication skills at SMAN 8 Malang. Quasi-experimental research uses pretest-posttest control groups design was chosen as research design in this study. The research sample was sixty-one 11th grade students taken by simple random sampling. Data were obtained through essay test, questionnaires and observation. Data analysis uses analysis of covariance (ANCOVA) to confirm the data against the proposed hypothesis. The results showed that there was a significant effect of the remap-tps learning model assisted wizer.me and MindMup on communication skills with an increase of 54.83%. The results of the analysis can be concluded that the learning model applied is effective in improving students’ communication skills. Thus, the Remap-TPS learning model assisted wizer.me website and MindMup application is recommended to develop students’ 21st century skills.